Surveillance of gynecologic cancer patients post-COVID-19 vaccine: Are CA-125 levels reliable? - Elizabeth Thayer; Lindsay Walsh; Katherine Leung; Sharmilee Korets (Elsevier, 2023)
Objective: The COVID-19 vaccine is known to instigate an inflammatory response that impacts cancer testing. We aimed to evaluate carbohydrate antigen 125 (CA-125) trends in gynecologic oncology patients in surveillance following COVID-19 vaccination to inform clinical practice. Methods: This was a single institution retrospective study of patients who received a COVID-19 vaccine while undergoing surveillance of gynecologic cancers with serial serum CA-125 measurements. CA-125 levels from the three months before and after vaccination were included in analysis. Differences between mean and median pre- and post-vaccination CA-125 levels for each patient were calculated. The mean and median of these differences were calculated, as well as the distribution of change. Demographic and cancer-related variables were also recorded. Results: Twenty-six patients who received a COVID-19 vaccine and were followed with surveillance serum CA-125 levels were identified. The mean age was 68.2 years; 92 % received a two-vaccine series. Forty-six percent had endometrial cancer and 54 % had ovarian cancer. The mean change from pre- to post-vaccine mean CA-125 level was 0.16 (±7.17) U/mL and the median change from pre- to post-vaccine median CA-125 level was −0.30 (IQR 3.66) U/mL. The range in change from pre- to post-vaccine mean was −16.50 to 24.00 U/mL, with 73 % of patients between −4 and +4 U/mL. Conclusion: We found no clinically significant change in CA-125 level after patients under surveillance for gynecologic cancers were vaccinated against COVID-19, suggesting that that the vaccine does not impact the utility of CA-125 as a tool to monitor disease in this population.